Effect of Social Capital on Organizational Performance of SMEs in Klang Valley, Malaysia - Othman, Shahrina; Hussin, Kasmaruddin Che; Isa, Nor Kalsum Mohd (CENTRAL ASIA AND THE CAUCASUS, 2021)
This study examined the direct relationships between social capital (SC) and organisational performance (OP). Studies have shown SC is a factor that contribute to this gap. The effect of IR4.0 and other megatrends make it even more challenging for these SMEs to prosper. Hence, SMEs require to make use of their full potential which includes adopting the best practices implemented in most develop countries, which is to increase the SC. This implementation validates new business models, the creation of new industries and redirecting of resources. The increasing rates of SC in the country can result in positive well-being functions, sustainability, and economic growth. Self-administered questionnaires were used to collect data from 500 SME manufacturing firms located in Klang Valley, in April and May 2018, and the gathered data was analysed by using SPSS 23.0. Statistically, the results confirmed that SC is positively related to SME performance. Civic Engagement and personal relationship contribute the most on OP. The outcome of this study provides new knowledge and important insights for government agencies to improve the policy to boost the performance of SMEs. Finally, in order to evaluate OP, it is more relevant to explore SEA, which needs encouragement to convert an organisation into a social organisation.